(3GdYhdeI GdEbJUGOjI (B:s (3efXeGJ, TQcGJgG, JOYjGJgG (B/s - (3YHO GdMejO, YHO GdeWdHs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2006)
(3GdJYQja HGdYhdeI GdEbJUGOjI hNUGFUgG(B- (3CfhGY GdYhdeI GdEbJUGOjI hGdYhGed GdeDOjI GdjgG(B- (3GdefXeGJ GdEbJUGOjI ddYhdeI(B- (3BdjGJ efXeI GdJLGQI GdYGdejI(B- (3GdTQcGJ eJYOOI GdLfSjGJ hGdYhdeI GdEbJUGOjI(B- (3eRjO ef GdCVhGA Ydi GdESJKeGQ GdGLfHj aj Xd GdYhdeI(B- (3bVGjG hCReGJ GdYhdeI GdEbJUGOjI(B- (3fXQI GSJTQGajI dJhLgGJ GdeXGgQGJ hGdMQcGJ GdefGgVI ddYhdeI GdEbJUGOjIs
Keywords: (3GdEbJUGOs; (3GdJLGQI GdYGdejIs; (3GdYhdeIs